1989
DOI: 10.1136/bjo.73.4.276
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology of trachomatous conjunctivitis.

Abstract: Upper palpebral conjunctival biopsy specimens obtained from eight patients with active trachoma were examined by routine histological and immunohistochemical methods. The epithelium expressed class I major histocompatibility complex (MHC) products throughout and class II MHC products in the superficial layers. The epithelial inflammatory infiltrate consisted of polymorphonuclear leucocytes, macrophages, T lymphocytes, and dendritic cells. In the underlying stroma the inflammatory infiltrate was organised as B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…2,4 Briefly, the inflammatory infiltrate in the epithelium consisted of large numbers of macrophages, T lymphocytes, polymorphonuclear leucocytes, and dendritic cells. The stromal inflammatory infiltrate was organized as lymphoid follicles and as a diffuse infiltrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,4 Briefly, the inflammatory infiltrate in the epithelium consisted of large numbers of macrophages, T lymphocytes, polymorphonuclear leucocytes, and dendritic cells. The stromal inflammatory infiltrate was organized as lymphoid follicles and as a diffuse infiltrate.…”
Section: Resultsmentioning
confidence: 99%
“…In previous immunohistochemical studies, we demonstrated the presence of increased numbers of activated macrophages in the conjunctival biopsy specimens from patients with active trachoma. 2,3 These macrophages showed cytoplasmic expression of the fibrogenic cytokines interleukin-1a, interleukin-1b, tumor necrosis factor-a, and platelet derived growth factor. 3 In the normal conjunctiva, there was no immunoreactivity for CTGF and bFGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It begins in the form of follicular conjunctivitis (active follicular trachoma), with papillary hypertrophy and inflammatory cells infiltrating the conjunctiva (lymphocytes, macrophages, neutrophils, and plasma cells) punctuated by lymphoid follicles (B cells surrounded by a mantle of T0 cells ) [23], which extends throughout the conjunctiva, especially in the upper tarsal conjunctiva.…”
Section: Pathophysiologymentioning
confidence: 99%
“…7 We propose that chlamydial modulation of host cytoskeleton may constitute a mechanism of immune-modulation. Because tissue damage in the form of scarring of genital, ocular or bronchial mucosal epithelia is due mostly to inflammation, 19,20 a detailed understanding of factors governing pathogenic vacuole stability will offer new insights into the interaction of Chlamydiae with host innate immune pathways.…”
Section: The Stability Of the Inclusion Is Linked To Immune-evasion Bmentioning
confidence: 99%